2014
DOI: 10.1002/ijc.29354
|View full text |Cite
|
Sign up to set email alerts
|

Screening outcome and surgical treatment during and after the transition from screen‐film to digital screening mammography in the south of The Netherlands

Abstract: We determined screening outcome of subsequent screens during and after the transition from screen-film mammography (SFM) to full-field digital mammography (FFDM). A consecutive series of 102,863 subsequent (SFM screens with a prior SFM screen (SFM-SFM cohort), 91,941 FFDM screens with a prior SFM screen (FFDM-SFM cohort) and 90,407 FFDM screens with a prior FFDM screen (FFDM-FFDM cohort) were obtained between January 2006 and July 2013. The referral rate and cancer detection rate (CDR) per 1,000 screens were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Weber et al . also found that the recall rate for suspicious calcifications remained significantly higher at digital screening, resulting in a permanently higher CNB rate for these lesions per 1,000 screens, compared to the period of screen‐film mammography . We observed a significant increase in the number of asymmetries as mammographic abnormality during the last 3 years of inclusion, as well as a significant decrease in the number of suspicious masses as reason for recall.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Weber et al . also found that the recall rate for suspicious calcifications remained significantly higher at digital screening, resulting in a permanently higher CNB rate for these lesions per 1,000 screens, compared to the period of screen‐film mammography . We observed a significant increase in the number of asymmetries as mammographic abnormality during the last 3 years of inclusion, as well as a significant decrease in the number of suspicious masses as reason for recall.…”
Section: Discussionsupporting
confidence: 49%
“…Communication between radiologists, pathologists and surgical oncologists is crucial to determine whether a high‐risk lesion should either be monitored by regular radiologic follow‐up imaging or whether excision can be considered. Stereotactic core needle biopsy (SCNB) is performed more often since the introduction of digital mammography in breast cancer screening, probably because digital mammography has a higher sensitivity for the detection of small calcifications compared to screen‐film mammography . It is not clear, however, to which degree high‐risk lesions are more frequently diagnosed in screened women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported a higher cancer detection rate during the transition from screen-film to full-field digital screening mammography [5], and this finding persisted in the second round of digital screening [10]. This increased detection rate, however, came along with more false-positive screen results and therefore a decreased positive predictive value of recall.…”
Section: Discussionmentioning
confidence: 99%
“…Details on screening outcome at screen-film mammography screening and the 1st and 2nd round of digital screening have been published previously [3, 10]. The transition from screen-film to digital screening mammography may increase the proportion of ductal carcinoma in-situ (DCIS) and smaller invasive cancers at the first digital screening round [3, 4, 11], but does not appear to result in a change of the tumor characteristics of the interval cancers [4, 5].…”
Section: Introductionmentioning
confidence: 99%